Isolation of probiotics Lactobacillus acidophilus from commercial yoghurt - Hassan, Hassan Pyar Ali (Author) (مجلة الأندلس للعلوم الاجتماعية والتطبيقية, 2023)
Probiotic Lactobacillus strain isolated from yogurt, after enrichment in MRS broth, was identified using a rapid screening method. The lactobacillus strain was identified as Lactobacillus acidophilus. The viable number of the cell in the yogurt was about 107 CFU/ml.